The Effect of the Realistic Mathematics Education (RME) Learning Model Assisted by Stick Media on Understanding the Concept of Multiplication - Azzahra Septia Hanami; Neha Nurabkafiya (GENFABET: Generasi Pendidikan Dasar, 2026)
This study is grounded in the need to enhance students’ conceptual understanding of multiplication, which often remains procedural and lacks meaningful comprehension at the elementary level. The research aimed to examine the effect of the Realistic Mathematics Education (RME) model assisted by stick media on students’ understanding of multiplication concepts. A quantitative approach with a quasi-experimental design was employed, involving 64 elementary school students divided into an experimental group and a control group. Data were collected using a validated post-test instrument measuring conceptual understanding. Data analysis techniques included descriptive statistics, Pearson correlation, and simple linear regression to determine the strength and significance of the relationship and predictive contribution of the independent variable. The findings indicate that students taught using the RME model assisted by stick media achieved higher post-test scores compared to those receiving conventional instruction. The regression analysis demonstrates a strong and significant positive effect of the RME model on conceptual understanding, with a substantial proportion of variance explained by the model. These results confirm that contextual learning integrated with concrete manipulatives enhances students’ ability to construct mathematical meaning. The study contributes empirically to the development of mathematics learning strategies by demonstrating the effectiveness of combining RME principles with simple, low-cost media. Its added value lies in providing a practical and theoretically grounded instructional alternative that can be readily implemented to strengthen conceptual learning in elementary mathematics.